RETRACTED: Studying the interaction between the new neodymium (Nd) complex with the ligand of 1,10-phenanthroline with FS-DNA and BSA - Raeisi Vanani, Ahmad; Asadpour, Saeid; Aramesh-Boroujeni, Zahra; Mobini Dehkordi, Maryam (Frontiers in Chemistry, 2023)
To learn more about the chemotherapeutic and pharmacokinetic properties of a neodymium complex containing 1,10-phenanthroline (dafone), In vitro binding was investigated with bovine serum albumin and fish-salmon DNA, using a variety of molecular modeling research and biophysical approaches. A variety of spectroscopic techniques including fluorescence and absorption were used to investigate the interplay between DNA/BSA and the neodymium complex. The findings revealed that the Nd complex had a high affinity for BSA and DNA interplays through van der Waals powers. In addition, the binding of the Nd complex to FS-DNA mainly in the groove binding mode clearly reflects with iodide quenching studies, ethidium bromide (EtBr) exclusion assay, ionic strength effect, and viscosity studies. It was observed that the Nd complex binds to FS-DNA through a minor groove with 3.81 × 105 (M-1). Also, Kb for BSA at 298 K was 5.19×105 (M-1), indicating a relatively high affinity of the Nd complex for DNA and BSA. In addition, a competitive study of a docking investigation revealed that the neodymium complex interacts at BSA site III. The results obtained from the binding calculations are well consistent with the experimental findings. Also, cytotoxicity studies of Nd complex were performed in MCF-7 and A-549 cell lines and the results show that this new complex has a selective inhibitory effect on the growth of various cancer cells.